Validation of the Teachers’ Digital Competence Instrument Using Rasch Measurement Model - Yuanyuan, Peng; Alias, Bity Salwana; Mansor, Azlin Norhaini; Nasir, M. Khalid M. (Journal of Ecohumanism, 2024)
Digital competence (TDC) is essential for the effective integration of technology in education and is widely recognized as a key factor in fostering high-quality educational environments. Empirical studies consistently demonstrate that TDC is a significant predictor of technology integration, underscoring the importance of assessing and enhancing TDC. To address this, the DigCompEdu framework and its CheckIn Self-reflection Tool were developed, offering a robust measurement for evaluating TDC. While this tool has been validated in various international contexts, its application within the Chinese educational system, particularly in higher vocational and technical colleges (HVTCs), has not been explored using the Rasch measurement model. This study addresses this gap by adapting and validating the DigCompEdu CheckIn tool for the Chinese context using Rasch analysis. The instrument, covering six domains of the DigCompEdu framework—Professional Engagement, Digital Resources, Teaching and Learning, Assessment, Empowering Learners, and Facilitating Learners’ Digital Competence—was culturally adapted and piloted with 417 teachers from Sichuan HTVCs. Rasch analysis confirmed that the adapted TDC instrument met all psychometric criteria, demonstrating strong reliability and validity. The validated instrument provides a reliable tool of TDC in Chinese HVTCs, supporting efforts to enhance digital competence and promote effective technology integration in teaching practices.